PENERAPAN TEORI PEMBANGUNAN JEMAAT DALAM PEDOMAN DASAR PELAYANAN PASTORAL PAROKI KEUSKUPAN AGUNG SEMARANG - Sugiyana Sugiyana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
The Semarang Archdiocese has developed a pastoral guideline for parishes in the Semarang Archdiocese. These guidelines are the Basic Guidelines for Parish Pastoral Services. This manual was prepared as part of the parish development effort. The pastoral guidelines contain a description of the parish, parish pastoral ministries with all their roles and duties, institutional structure and forms of coordination, service mechanisms and various supports and other facilities. What underlies the preparation of these guidelines? What factors are included in the guideline? Does the selection of these factors take into account the theory of church building? From research using a literature approach, the results show that the preparation of the guidelines has a theoretical framework for church development. The five factors contained in Jan Hendriks' Congregational Development theory are contained and well developed in the Basic Guidelines for Parish Pastoral Services. The guidelines contain a positive climate, leadership, structure, goals and tasks as well as self-concept. If these guidelines are followed properly, parishes can develop into vital and attractive parishes, where people participate happily and with benefit for themselves and for the congregation.